2014
DOI: 10.13183/jcrg.v3i1.106
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms Among Survivors of Burn Injuries

Abstract: Ab s t r a c tPurpose: To estimate the prevalence of depressive symptoms in patients surviving a burn injury. Methods:A descriptive cross-sectional study was conducted on 100 burn inpatients (50 males and 50 females) admitted to Sina Burn Center; Tabriz University of Medical Sciences during 2012.The severity and grade of burn injury was evaluated by a dermatologist. Beck Depression Inventory (BDI-II) was used to evaluate the existence and severity of depressive symptoms. Results:In this study, 56% of burn pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Alvi et al from WahCantt also reported flam burns predominating cause of burn among the targeted population which is consistent to our findings. Another study from Iran conducted by 3 Afraie et al reported 84 % flame burn injuries, which is in compliance with our study results. Depression was noted in 88 (58.7%) of our study 9 cases.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Alvi et al from WahCantt also reported flam burns predominating cause of burn among the targeted population which is consistent to our findings. Another study from Iran conducted by 3 Afraie et al reported 84 % flame burn injuries, which is in compliance with our study results. Depression was noted in 88 (58.7%) of our study 9 cases.…”
supporting
confidence: 93%
“…Psychological impairment has found to be present in 45.5% and 40% at baseline and follow up 8 9 assessments respectively. Alvi et al from WahCantt reported 58 % depression in burn patients while another study from conducted by 3 Afraie et al reported 56 % depression in burn patients. There is only one study done in Pakistan to document depression in burn patients, which was done using a very small sample size of only 50 patients, so the results of this one study done with a small sample size could not be generalized on our large number of burns patients in Southern Punjab.…”
Section: Introductionmentioning
confidence: 95%